نظام الحسبة، مظهرٌ من مظاهر واقعية الحضارة الإسلامية وبعدها الإنساني - كرطالى,أمين (University of Eloued جامعة الوادي, 2024)
نظام الحسبة، مظهرٌ من مظاهر واقعية الحضارة الإسلامية وبعدها الإنساني) ملخص: يعتبر نظام الحسبة أحد تلك الأنظمة الدينية ذات طابع اجتماعي والتي أبدعتها الحضارة الإسلامية، وكان لهذا النظام دور بارز في حماية القيم الدينية والأخلاقية للمجتمعات الإسلامية، كما اتّسم هذا النّظام الفريد بالواقعية وبعده الإنساني، وهو ما تجلّى في حمايته للحقوق والأخلاق والمكتسبات، والدّمج بين الوعظ والرّدع. كما أنّ هذا النظام جسّد مبدأ الأمر بالمعروف والنهي عن المنكر من خلال الممارسة الميدانية، وبذلك تداخلت مهام المحتسب أحيانا مع مهام القاضي، لا سيما قاضي المظالم، وأيضا مع نظام الشرطة في بعض الأحيان. The Hisbah system is one of the religious systems with a social character that was created by Islamic civilization. This system played a prominent role in protecting the religious and moral values of Islamic societies. This unique system was characterized by realism and its human dimension, which was evident in its protection of rights, morals and gains, and the integration of preaching and deterrence. This system also embodied the principle of enjoining good and forbidding evil through field practice, and thus the duties of the Hisbah sometimes overlapped with the duties of the judge, especially the grievance judge, and also with the police system at times.
Keywords: الحسبة; الأحكام السلطانية; السياسة الشرعية; الحضارة; Hisbah; Islamic systems; Human rights; Royal rulings; Consumer protection